Application and Empirical Analysis of Asset Pricing Models in the Chinese Stock Market - Yue, Qiannian (International Journal of Global Economics and Management, 2024)
This paper examines the application and performance of asset pricing models in the Chinese stock market. We analyze the Capital Asset Pricing Model (CAPM), the Fama-French Three-Factor Model, and the Carhart Four-Factor Model, assessing their effectiveness in explaining stock returns within the context of China's unique market environment. Using data from major Chinese stock exchanges, we employ regression analysis to evaluate the models. Our findings reveal that multifactor models, particularly the Carhart model, provide superior explanatory power compared to CAPM, highlighting the importance of incorporating additional risk factors. This study contributes to the understanding of asset pricing in emerging markets and offers practical insights for investors and policymakers.